Interrelation of types of visual activity of younger schoolchildren (Pedagogy of Higher and Secondary Education, 2011)
In this article the problem of defining elementary school children’s visual art concept essence, its expressive means have been analyzed; peculiarities and possibilities of its forms’ interactions are exposed.
Keywords: visual art; the expressive means; applique; painting; design; modeling